Griseofulvin dissolved in binary aqueous co-solvent mixtures of N, N-dimethylformamide, methanol, ethanol, acetonitrile and N-methylpyrrolidone: Solubility determination and thermodynamic studies. (December 2020) - Zhao, Xi; Farajtabar, Ali; Han, Gui; Zhao, Hongkun
Graphic abstract: Highlights: Solubility of griseofulvin in five aqueous mixtures was determined and correlated. Preferential solvation of griseofulvin were derived via IKBIs method applied to solubility. Solvent effect upon solubility variation was investigated by KAT-LSER model. Abstract: The equilibrium solubility of griseofulvin in five co-solvent mixtures of N, N -dimethylformamide (DMF) + water (2), methanol (1) + water (2), ethanol (1) + water (2), acetonitrile (1) + water (2) and N -methylpyrrolidone (NMP) (1) + water (2) were acquired through experiment at temperatures covering from 278.15 K to 323.15 K by the saturation shake-flask technique. The maximum solubility appeared in the neat co-solvents of DMF/methanol/ethanol/acetonitrile/NMP for each mixture. The mole fraction solubility of griseofulvin in the five mixtures was well correlated via van't Hoff–Jouyban-Acree model and Jouyban-Acree model acquiring values of relative average deviations<9.41% and root-mean-square deviations<10.30 × 10 -4 . The cavity term and KAT parameters correlated the mole fraction solubility in terms of the linear solvation energy relationships. The significant effect to the solubility variation was the cavity term and dipolarity-polarizability term in aqueous DMF/methanol/ethanol/acetonitrile/NMP mixtures. What's more, the quantitative magnitudes for local mole fractions of DMF/methanol/ethanol/acetonitrile/NMP and water around the drug griseofulvin were evaluated by using the Inverse Kirkwood–Buff integrals method applied to griseofulvin solubility. In the methanol (1) + water (2) mixture with compositions 0.31 < x 1 < 1, ethanol (1) + water (2) mixture with compositions 0.25 < x 1 < 1, DMF (1) + water (2) mixture with compositions 0.20 < x 1 < 1, NMP (1) + water (2) mixture with compositions 0.16 < x 1 < 1 and acetonitrile (1) + water (2) mixture with compositions 0.253 < x 1 < 1, griseofulvin was preferentially solvated by DMF/methanol/ethanol/acetonitrile/NMP.